(untitled) (Pragyaratna प्रज्ञारत्न, 2024)
Grounded in the socio-cultural theory (SCT) of learning, this study postulates that cognitive development is intricately tied to social interactions, highlighting the significance of cultural and social contexts in shaping an individual’s learning experiences and intellectual growth. Utilizing the content analysis methodology, the study systematically analyzes three key constructs—social interaction, the more knowledgeable other (MKO), and the zone of proximal development (ZPD)—drawing from Vygotsky’s seminal works to contextualize these constructs to enhance the language teaching and learning process within the specific cultural framework of Nepal. The findings reveal insights into the application of SCT in Nepalese language education. Social interactions, crucial in Vygotsky’s theory, find significance in Nepal’s communal spirit, influencing language learning positively. MKOs, both human and symbolic, play an essential role in shaping language learning, aligning with Nepalese values and linguistic diversity. The ZPD framework is applicable in Nepal’s diverse educational landscape, addressing individual differences and accommodating cultural nuances in which the scaffolding technique has a fundamental role in bridging linguistic gaps and fostering a collective journey toward linguistic proficiency. Overall, Vygotsky’s SCT demonstrates relevance and adaptability in the unique cultural and linguistic context of Nepal, offering insights into educational policies and practices.